Driving workload indicators: the case of senior drivers - Costa, Nélson Bruno Martins Marques da (2018)
The automotive industry is currently focused in the goal of developing advanced autonomous driving systems (ADAS) and its supporting technologies. A main condition for achieving this goal is to ensure drivers’ safety and comfort during the ride. The driving task is often described as complex and dynamic and can be considered as the single most risky task that the individual has to perform on a daily basis. Since the mean age of the population in industrialized countries is gradually increasing, one of the ADAS objective is to enhance mobility of seniors by easing the task of driving to levels with which they are able to comply. This paper aimed at researching present key workload indicators that can be used by the car autonomous driving systems to establish the more efficient means to keep the senior drivers informed about the driving task and surrounding environment, allowing them to benefit from other entertainment applications and safely resume the driving task.